PENGARUH LAMA FERMENTASI DENGAN BIOAKTIVATOR EM4 TERHADAP KANDUNGAN N DAN C/N PUPUK BOKASHI AMPAS TEBU (Saccharum officinarum L) - Siti Asih Priyati; Suwondo Suwondo; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Bagasse is a waste resulting from the production of sugarcane stems which can be used as compost. The composting process uses an EM4 bioactovator to speed up the composting process. In the composting process will occur fertilizer fermentation process. This study aims to determine the effect of fermentation time of sugarcane bagasse (Saccharum officinarum L) fertilizer on N and C/N content. This research is an experimental study in August-October 2021. Experiment with a Completely Randomized Design (CRD) with 4 treatments and 3 repetitions. The data will be analyzed using ANOVA. If there are differences in the data, an LSD follow-up test will be carried out at the 0.05% level. The treatment was in the form of long fermentation, namely 14 days, 21 days, 28 days and 35 days of fermentation. The parameters observed were N and C/N levels, temperature, humidity and pH. The results showed that the duration of fermentation with the EM4 bioactivator affected the levels of N and C/N of sugarcane bagasse bokasi fertilizer (Saccharum officinarum L). The highest N and C/N content was found at 35 days of fermentation.Key Words : Bagasse, EM4, Fermentation Time, N and C/N.